2014
DOI: 10.1063/1.4873802
|View full text |Cite
|
Sign up to set email alerts
|

Foam injection moulding of a TPO/TPC-blend and the effect of different nucleating agents on the resulting foam structure

Abstract: Germany -johannes.mueller@nmbgmbh.de; andreas.spoerrer@nmbgmbh.de; volker.altstaedt@nmbgmbh.de Abstract The manufacturing of car interior parts with a soft touch surface is possible in a one-step injection moulding process, in which an injection moulded carrier is overmoulded with a compatible foamed thermoplastic elastomer (TPE). In contrast to the complex conventional process the structural foaming of the TPE component allows a saving of one material component as it combines a compact skin and a foamed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Leung et al [84] showed that additives with many crevices of small semiconical angles lead to higher quality polymer foams, with a high cell density, a smaller cell size and narrower cell size distribution. Some of the most common fillers, namely talc, calcium carbonate, mica and carbon fibers have been successfully employed to the formation of fine and uniform cell morphologies [179,180,182,[267][268][269][270][271], as well as wood fibers, clay and rubber particles [162,163,165,178,182,184,[272][273][274]. Glass fibers (GF) have been traditionally utilized in many industrial applications due to the increase in stiffness and strength of reinforced thermoplastics, creep resistance and service temperature [275].…”
Section: Chapter 5: Pp 20gf -Mucell® Foamsmentioning
confidence: 99%
“…Leung et al [84] showed that additives with many crevices of small semiconical angles lead to higher quality polymer foams, with a high cell density, a smaller cell size and narrower cell size distribution. Some of the most common fillers, namely talc, calcium carbonate, mica and carbon fibers have been successfully employed to the formation of fine and uniform cell morphologies [179,180,182,[267][268][269][270][271], as well as wood fibers, clay and rubber particles [162,163,165,178,182,184,[272][273][274]. Glass fibers (GF) have been traditionally utilized in many industrial applications due to the increase in stiffness and strength of reinforced thermoplastics, creep resistance and service temperature [275].…”
Section: Chapter 5: Pp 20gf -Mucell® Foamsmentioning
confidence: 99%
“…According to the classical nucleation theory explained in Chapter 2 [83], undissolved gas trapped at the filled/polymer interface promotes the occurrence of multitude of sites for cell formation requiring much lower activation energy for bubble nucleation, accelerating cell nucleation and the development of a large number of cells with small cell size. Moreover, the added fillers increase melt strength of the material [267],…”
Section: Morphology and Apparent Densitymentioning
confidence: 99%